Multi detector computed tomography evaluation in chronic obstructive pulmonary disease and correlation with severity of disease - Kumar, Ajay; Rohira, Ankita; Vijay, Ashish; Sharma, Abhay (International Journal of Research in Medical Sciences, 2019)
Background: Multi Detector computed tomography (MDCT) may effectively characterize and quantify the extent of emphysema and the air trapping related to the small airway’s disease. Here we highlight the computed-tomography findings of Chronic Obstructive Pulmonary Disease (COPD) and correlation with the Spirometrics values. Methods: The study group included the total of 100 adult patients of either sex with a clinical suspicion of COPD and those who undergone MDCT of thorax. Lung function of the patients with the COPD stages mild to very severe was evaluated by both the MDCT and Spirometrics Pulmonary Function Tests (PFTs). The scanning was done at maximum end inspiration and maximum end expiration. Results: There was a preponderance of male patients with highly significant correlation between values of mean lung density and low attenuation values (p<0.000I). MDCT correlated well with those obtained from spirometric Pulmonary Function Tests in the patients with COPD and that the correlation at expiration was superior to that at inspiration. Conclusions: The study concludes that Multi-detector computed tomography is the invaluable tool in defining and quantifying COPD and the characterization of emphysematous changes.